METHODOLOGICAL ISSUES OF BANKING OPERATIONAL RISK MANAGEMENT - David I. Philippov (Статистика и экономика)
The article highlights the issues of operational risk management methodology in commercial bank. The main sources of operational risks, risk indicators, operational risk assessment techniques.